Taxonomic status of Oenocarpus bataua (Euterpeae, Arecaceae) inferred from plastid sequences - Montúfar, Rommel (2008)
With the aim of testing the evolutionary relationships between Oenocarpus bataua (formerly Jessenia bataua) and other Oenocarpus species (Arecaceae), a phylogenetic study of tribe Euterpeae (Arecaceae) was conducted using 3,6 kb of non-coding chloroplast DNA sequence data. The results of maximum parsimony analysis support the monophyly of Euterpeae and the inclusion of O. bataua within the Oenocarpus clade. Our results show substantial molecular divergence between O. bataua var. bataua and var. oligocarpus suggesting that, according to their original description, these two taxa may indeed represent different species. However, our phylogenies should be considered as tentative due to low statistical support.